Tuberculosis-triggered cytokine storm with hemophagocytic lymphohistiocytosis and tuberculous spondylitis in an apparently immunocompetent host: a case report and literature review - Zhu, Liya; Lu, Jinzhi; Chen, Yanfei (Frontiers in Immunology, 2025)
Hemophagocytic lymphohistiocytosis (HLH) secondary to disseminated tuberculosis (TB) is a rare, life-threatening hyperinflammatory syndrome. We present a 60-year-old man with recurrent fever and syncope. Workup revealed cytopenias, hyperferritinemia (peak 5,802 ng/mL), elevated C-reactive protein (CRP), and hepatic dysfunction, fulfilling HLH-2004 criteria. Imaging showed miliary lung nodules and tuberculous spondylitis at T9. Bone marrow biopsy confirmed hemophagocytosis, and next-generation sequencing identified Mycobacterium tuberculosis. This case demonstrates that disseminated TB can trigger a fulminant cytokine storm even in an elderly host without overt immunodeficiency. Successful outcomes require combined antitubercular and immunomodulatory therapy.